Cobalt(iii)-catalyzed C–H halogenation of 6-arylpurines: facile entry into arylated, sulfenylated and alkoxylated 6-arylpurines. Issue 12 (2nd March 2016) - Pawar, Amit B.; Lade, Dhanaji M.
Abstract : Cp*Co(iii )-catalyzed C–H halogenation of 6-arylpurines has been reported under mild conditions and this protocol was further applied for the synthesis of arylated, sulfenylated and alkoxylated purine analogues. Abstract : Cobalt-catalyzed C–H halogenation of biologically important 6-arylpurines has been reported under mild conditions with good functional group tolerance. The regioselective halogenation of thiophenes, as well as the synthetic applicability of the present protocol for the synthesis of arylated, sulfenylated and alkoxylated purine analogues was also demonstrated.